Polyphenols from foxtail millet bran ameliorate DSS-induced colitis by remodeling gut microbiome - Yang, Ruipeng; Shan, Shuhua; An, Ning; Liu, Fengming; Cui, Kaili; Shi, Jiangying; Li, Hanqing; Li, Zhuoyu (Frontiers in Nutrition, 2022)
It has been known that polyphenols from plants possess the anti-inflammatory and gut microbiota modulated properties. Foxtail millet (Setaria italica L., FM) has potential medical and nutritional functions because of rich phenolic and other phytochemical components. Here, the study explored the effects of bound polyphenol of FM bran on dextran sodium sulfate (DSS)-induced experimental colitis mice. Results showed that BPIS administration effectively relieved the weight loss, decreased disease active index (DAI) scores, restrained the secretion of pro-inflammatory cytokines TNF-α, IL-6 and IL-1β, increased anti-inflammatory cytokines IL-10, IL-4, IL-5. BPIS prevented gut barrier damage by enhancing tight junction proteins Claudin1, ZO-1 and Occludin, increasing the number of goblet cells and facilitating the gene expressions of mucin family. In addition, BPIS restored the gut microbiota composition and increased the relative abundance of commensal bacteria such as Lachnospiraceae and Rikenellaceae and restrained the growth of S24-7 and Staphylococcaceae. Concentrations of short-chain-fatty acids (SCFAs) generated by gut microbiota were elevated in BPIS treated colitis mice. These data suggest that BPIS effectively ameliorates DSS-induced colitis by preventing intestinal barrier damage and promoting gut microbiota community.